Formability of automotive steels using forming limit diagrams - Ozcan, Elvin; Bakkaloglu, Adem (CARL HANSER VERLAG, 2016)
Using forming limit diagrams is the most convenient method for determining the forming limits of steel sheets. In this work, they were investigated primarily. Six diagrams were prepared for five different steel grades having different properties and then the effects of sheet thickness, r values, chemical and mechanical properties were compared for the forming limits by using these diagrams. The results revealed that the forming limit curves are shifted towards higher limit strains with the increase of the sheet thickness. Also, it was found that higher r values have a favorable effect on the limit strain values as indicated in the literature. Finally, it was seen from the diagrams that increasing of carbon ratio and strength properties has a negative impact on the formability.
Keywords: Formability; FLD; forming limit diagrams; automotive steels; Materials Science